Pengaruh Pemberian Onggok Yang Difermentasi dengan Limbah Cumi-Cumi (Sepia sp) pada Kinerja Pertumbuhan Ikan Nila (Oreochromis niloticus) dengan Pemberian Onggok Yang Difermentasi dengan Limbah Cumi-Cumi (Sepia sp) - Cahyono, Indra; Rahmat, Nur; Nursyahran, Nursyahran; Mulyani, Sri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
This study aims to evaluate the effect of fermented cassava with squid tapioca waste on the growth, survival, and feed quality of earthworms (Lumbricus rubellus) and tilapia (Oreochromis niloticus). This study used a Completely Randomized Design (CRD) with three treatments, namely the concentration of fermented cassava (10 ml, 15 ml, and 20 ml) in varying tapioca waste. The results showed that the highest specific growth rate (SGR) and increase in body length of earthworms were found in the treatment of fermented cassava 20 ml (treatment C) with values ​​of 4.40% and 19.2 mm respectively and the highest survival rate (SH) of 89.16%. Earthworm feed fermented cassava also had a positive effect on the growth of tilapia with the highest SGR value in treatment C of 1.17% and the survival rate of tilapia reaching 93.33%. Water quality parameters throughout the study remained within the optimal range for both organisms, with temperature, pH, and dissolved oxygen levels suitable for tilapia growth. This study concluded that fermentation of tapioca waste with squid by-products can improve feed quality, accelerate growth, and increase the survival rate of earthworms and tilapia, making it a sustainable alternative feed source in tilapia cultivation